2011
DOI: 10.1021/bi200215j
|View full text |Cite
|
Sign up to set email alerts
|

A Universal Method for Detection of Amyloidogenic Misfolded Proteins

Abstract: Diseases associated with the misfolding of endogenous proteins, such as Alzheimer’s disease and type II diabetes, are becoming increasingly prevalent. The pathophysiology of these diseases is not totally understood, but mounting evidence suggests that the misfolded protein aggregates themselves may be toxic to cells and serve as key mediators of cell death. As such, an assay that can detect aggregates in a sensitive and selective fashion could provide the basis for early detection of disease, before cellular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 55 publications
2
47
0
Order By: Relevance
“…[33][34][35] On the other hand, SPR imaging is ar eal-time, label-free, and high-throughput method. Zhao et al combined the specific recognition of peptoid (ADP3) and the advantages of SPR imaging to detect serum Ab .…”
Section: Surfaceplasmon Resonance Sensorsmentioning
confidence: 99%
“…[33][34][35] On the other hand, SPR imaging is ar eal-time, label-free, and high-throughput method. Zhao et al combined the specific recognition of peptoid (ADP3) and the advantages of SPR imaging to detect serum Ab .…”
Section: Surfaceplasmon Resonance Sensorsmentioning
confidence: 99%
“…Peptoids are promising materials for biomedical and nanoscience research because they are robust and synthetically flexible yet sequence-specific and highly tunable 5 . Peptoids have demonstrated biological activity (therapeutics 6,7 , diagnostics 8 , intracellular delivery [9][10] ) and folding into hierarchical nanostructures 3,[11][12][13][14] …”
Section: Applications and Significancementioning
confidence: 99%
“…in today's world. [1][2][3][4][5] Misfolded proteins have the potential to interact with one another creating toxic aggregates, amyloids, which are most commonly known for fibril accumulation and an increase in b-sheet content.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Recent studies have also shown that AD can occur without the presence of fibril plaques and suggest that the small soluble Ab oligomers are the likely neurotoxic agent that is associated with the progress of AD. 1,6,[9][10][11][12][17][18][19][20] The formation of oligomers are believed to be intracellular and can potentially affect synapse functions, disruption of glutamate uptake, and prevent the ability to maintain proper memory. 1,3,17,21 Since the oligomer aggregates are unstable and time dependent, the exact shape, size, and pathological pathway are hard to determine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation